Potential Analysis of the Sumberringin River for a Micro Hydro Power Plant in Tumpang District, Malang Regency - Hanggara, Ikrar; Arystianto, Deni Putra; Susilo, Helik (Universitas Tribhuwana Tunggadewi Malang, 2023)
The Sumberringin River is included in the upstream section so that the shape of the land surface around the river is still a hilly area, so it has a narrow river dimension with a reasonably high flow velocity. This condition is interesting for conducting studies related to the potential of the river supported by the existence of the Wringinsongo area, which relies on flowing water sources as tourism. This study aims to determine : 1) the potential of the Sumberringin River in the form of river water discharge, 2) the elevation of the land surface to obtain a high potential for falling for the potential energy utilization of river water, 3) the shape of the land surface (land-surface) for modeling river utilization construction, 4) The potential amount of electrical power that can be generated theoretically using a micro-hydro power plant (PLTMH). This study used a survey method of measurement/observation of two biological parameters (water flow discharge and ground elevation/falling height of river water flow) to simulate potential water flows and model the construction of the PLTMH building. River discharge measurements are carried out at four points in the location as a reference for calculations. The first point is ninety liters per second; the second is one hundred and forty liters per second; the third is thirty liters per second; and the fourth is eight twenty liters per second, so the average measured flow rate is eighty liters per second. The results of contour modeling show that the height of the fall is 3-3 meters high, the width of the planned weir is five and a half meters, with a weir height of one and a half meters, it is planned to be able to generate electricity in a turbine of eleven kilowatts using a crossflow type turbine. This research can be a comparison method for other similar areas in calculating river potential.ABSTRAKSungai Sumberringin termasuk pada bagian hulu sehingga bentuk permukaan tanah sekitar sungai masih merupakan daerah perbukitan, sehingga memiliki dimensi sungai yang tidak lebar dengan kecepatan aliran yang cukup tinggi. kondisi tersebut menarik untuk dilakukan kajian terkait potensi sungai ditunjang dengan keberadaan daerah wringinsongo yang mengandalkan aliran sumber air sebagai wisatanya. Penelitian ini bertujuan untuk mengetahui: 1) potensi sungai sumberringin berupa debit air sungai, 2) elevasi muka tanah untuk mendapatkan potensi tinggi jatuh untuk pemanfaatan energi potensial air sungai, 3) bentuk muka tanah (land-surface) untuk pembuatan model konstruksi pemanfaatan sungai, 4) potensi besaran daya listrik yang dapat dihasilkan secara teoritis menggunakan pembangkit listrik tenaga mikro-hidro (PLTMH). Penelitian ini menggunakan metode survei pengukuran / observasi terhadap dua parameter alam (debit aliran air dan elevasi muka tanah / ketinggian jatuh aliran air sungai) untuk kemudian dilakukan simulasi potensi aliran air dan pemodelan konstruksi bangunan PLTMH. Pengukuran debit sungai dilaksanakan pada empat titik di lokasi sebagai acuan perhitungan, titik pertama sebesar sembilan puluh liter per-detik, titik kedua sebesar seratus empat puluh liter per-detik, titik ketiga sebesar tiga puluh liter per-detik, titik ke-empat sebesar delapan puluh liter per-detik sehingga rerata debit aliran yang terukur sebesar delapan puluh liter per detik. Hasil pemodelan kontur didapatkan besarnya tinggi jatuh yang didapatkan setinggi 3 tiga meter, lebar bendung rencana sebesar lima setengah meter, dengan tinggi bendung sebesar satu setengah meter, direncanakan mampu untuk membangkitkan listrik pada turbin sebesar sebelas kilowatt menggunakan turbin tipe crossflow. Hasil penelitian ini dapat menjadi salah satu metode pembanding daerah lain yang sejenis dalam menghitung potensi sungai.